Potential Role of Extracellular CIRP in Alcohol-induced Alzheimer’s Disease - Sharma, Archna (Mol Neurobiol, 2020)
Alzheimer’s disease (AD) is the sixth leading cause of death in the US and the most common form of neurodegenerative dementia. In AD, microtubule-associated protein tau becomes pathologically phosphorylated and aggregated, leading to neurodegeneration and the cognitive deficits that characterize the disease. Prospective studies have shown that frequent and heavy alcohol drinking is linked to early onset and increased severity of AD. The precise mechanisms of how alcohol leads to AD, however, remain poorly understood. We have shown that extracellular cold inducible RNA binding protein (eCIRP) is a critical mediator of memory impairment induced by exposure to binge-drinking levels of alcohol, leading us to reason that eCIRP may be a key player in the relationship between alcohol and AD. In this review, we first discuss the mechanisms by which alcohol promotes AD. We then review eCIRP’s role as a critical mediator of acute alcohol intoxication-induced neuroinflammation and cognitive impairment. Next, we explore the potential contribution of eCIRP to the development of alcohol-induced AD by targeting tau phosphorylation. We also consider the effects of eCIRP on neuronal death and neurogenesis linking alcohol with AD. Finally, we highlight the importance of further studying eCIRP as a critical molecular mechanism connecting acute alcohol intoxication, neuroinflammation, and tau phosphorylation in AD along with the potential of therapeutically targeting eCIRP as a new strategy to attenuate alcohol-induced AD.